(Re)Defining Local Animation: An Exploration Of South African Animation In Terms Of Local Production, Local Relevance And Local Ownership - Rogerson, Arabella (Centre for Film and Media Studies, 2024)
There is a pressing need to better understand how we speak about South African animation and what we mean by it. This study interrogates three particular interpretations of South African animation in order to build a multifaceted and nuanced understanding of the industry, its outputs and its value. Using a qualitative research approach, this study investigates South African animation in terms of content that is made within South Africa, content that is relevant to South Africa and content that is owned by South Africa. In extension, this research underscores the intricate interplay between supply and demand factors, production conditions, and production environments that shape the dynamics of the local animation industry. This research offers a new framework for discussing animated texts from the lens of the production landscape which departs from the more prevalent textual analysis approach and discussions of narrative, iconography, and representation. Ultimately, this research serves to contribute towards the efforts to reposition Africa and its creative outputs within the global animation conversa